2000
DOI: 10.1161/01.str.31.9.2112
|View full text |Cite
|
Sign up to set email alerts
|

Piracetam Improves Activated Blood Flow and Facilitates Rehabilitation of Poststroke Aphasic Patients

Abstract: Background and Purpose-In a prospective, double-blind, placebo-controlled study, it was investigated whether piracetam improves language recovery in poststroke aphasia assessed by neuropsychological tests and activation PET measurement of cerebral blood flow. Methods-Twenty-four stroke patients with aphasia were randomly allocated to 2 groups: 12 patients received 2400 mg piracetam twice daily, 12 placebo. Before and at the end of the 6-week treatment period in which both groups received intensive speech thera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
72
1
8

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 162 publications
(84 citation statements)
references
References 36 publications
3
72
1
8
Order By: Relevance
“…The few available reports concern studies that have mainly focused on behavioral revalidation, with the exception of one report on neuroimaging and pharmacological therapy in aphasia (180). This placebo-controlled activation study demonstrated a significant improvement in patients treated with piracetam, a GABA derivative.…”
Section: Language Recovery Poststrokementioning
confidence: 99%
“…The few available reports concern studies that have mainly focused on behavioral revalidation, with the exception of one report on neuroimaging and pharmacological therapy in aphasia (180). This placebo-controlled activation study demonstrated a significant improvement in patients treated with piracetam, a GABA derivative.…”
Section: Language Recovery Poststrokementioning
confidence: 99%
“…Интересно, что прием пирацетама в тех же дозах в периоды между выполнением за-даний, то есть в состоянии покоя, не вызывал зако-номерных изменений ЭЭГ. Другая методика выбора доз пирацетама основывается на данных некоторых авторов [70,93] о том, что приоритетное значение в этом смысле имеет не суточная, а курсовая доза препарата.…”
Section: ■ таблица 4 дозирование пирацетама при почечной недостаточнunclassified
“…Дозировка пирацетама варьирует в соответствии с показаниями [67,70,82,93] Взрослым назначают пирацетам, начиная с су-точной дозы 1,2 г (по 0,4 г 3 раза в сутки), и доводят ее до 2,4 г, иногда до 3,2 г и более. Отчетливый тера-певтический эффект в этих случаях отмечается, как правило, через 2-3 недели от начала лечения.…”
Section: ■ таблица 4 дозирование пирацетама при почечной недостаточнunclassified
“…In general, this type of treatment strategy influences the neurotransmitters and facilitates recovery process of neural networks infrastructure of language processing (35). Positron Emission Tomography ( PET) studies indicate that aphasia recovery after taking these medicine facilitates and accelerates the reactivation of left hemisphere (36,37). Nevertheless, researchers have not attained specific biomarkers which can prove the pharmacotherapy efficiency on improvement of the neural circuitry associated with language (7).…”
Section: Introductionmentioning
confidence: 99%